A lithium-rich manganese-based composite lithium battery positive electrode material and a manufacturing method thereof

By adopting the lithium-rich manganese-based composite lithium battery positive electrode material, combined with nanodiamondole olefins and rare earth samarium compounds, the problem of poor structural stability of manganese-based positive electrode material is solved, and high specific capacity, stable electrochemical performance and suitable for industrial production are achieved.

CN110911663BActive Publication Date: 2025-04-25HUIZHOU UNIV

Patent Information

Application Number
CN201911107551.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-11-13
Publication Date
2025-04-25
Estimated Expiration
2039-11-13

AI Technical Summary

Technical Problem

The existing manganese-based positive electrode materials have poor structural stability during charging and discharging, and the cycle performance, rate performance and safety need to be improved.

Method used

The lithium-rich manganese-based composite lithium battery cathode material, including lithium-rich manganese positive electrode substrate with the molecular formula xLi2MnO3·(1-x)LiMO2, nanodiamondene, silica, iron oxide, ethylene glycol, solid paraffin and rare earth samarium compounds, were prepared through specific mixing, sintering and grinding processes.

Benefits of technology

A positive electrode material with high specific capacity (about 300mAh/g), high first cycle voltage (about 4.7V), and stable high-temperature cycle performance is achieved, which improves the electrochemical performance of the material and the applicability of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110911663B_ABST
    Figure CN110911663B_ABST
Patent Text Reader

Abstract

The invention provides a lithium-rich manganese-based composite lithium battery positive electrode material and a preparation method thereof. The materials include the following components: 5-100 parts of a lithium-rich manganese-based positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2, 1-10 parts of nanodiamondene, 1-15 parts of silicon dioxide, 2-5 parts of iron oxide, 1-50 parts of ethylene glycol, 1-2 parts of solid paraffin, and 0.5-2 parts of a rare earth samarium compound. The lithium-rich manganese-based composite lithium battery positive electrode material provided by the invention has the advantages of high specific capacity, a first cycle voltage of up to about 4.7V, stable high-temperature cycle performance, and the like. The invention has a simple process, low equipment strength requirements, a short production cycle, is suitable for industrial production requirements, and has great economic value and practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery material preparation, and in particular to a lithium-rich manganese-based composite lithium battery positive electrode material and a preparation method thereof. Background Art

[0002] In order to meet the needs of the power battery market, the energy density of lithium batteries must be improved. The future trend is mainly to develop in the direction of high specific energy and high discharge voltage. Among the manganese-based positive electrode materials, spinel LiMn2O4, layered LiMnO2 and layered solid solution positive electrode materials have been studied more. Among them, the layered LiMnO2 has poor structural stability during charging and discharging, and has not been studied much at present. Spinel LiMn2O4 can play a role in the two voltage ranges of 4V and 3V. For the 4V region, it is related to the embedding and extraction of lithium ions at the tetrahedral 8a position of the spinel structure; for the 3V region, it is related to the embedding and extraction of lithium ions at the octahedral 16c position of the spinel structure. The embedding and extraction of lithium ions at the tetrahedral position of the spinel structure will not cause obvious changes in the sample structure. However, when the depth of charge and discharge is too great, due to the John-Teller distortion effect of lithium ions, the embedding and extraction of lithium ions in the octahedron will cause the sample structure to change from cubic to tetragonal, and the discharge capacity will decay rapidly. With the development of science and technology, the lithium battery industry is also facing challenges and opportunities. How to make the power battery materials the best and achieve the best performance has become a hot topic in the lithium battery industry. Although the performance of lithium-manganese-rich positive electrode materials as positive electrode materials for power batteries has been greatly improved, their cycle performance, rate performance and safety still need to be further improved. Summary of the invention

[0003] In view of the above problems, the present invention provides a composite lithium battery separator with good tensile strength and high electrolyte absorption rate and a preparation method thereof.

[0004] The technical solution adopted by the present invention to solve the above problems is:

[0005] The present invention provides a lithium-rich manganese-based composite lithium battery positive electrode material, comprising the following raw materials: 5-100 parts of a lithium-rich manganese positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2,

[0006] Nanodiamondene 1-10 parts,

[0007] 1-15 parts of silicon dioxide,

[0008] 2-5 parts of iron oxide,

[0009] 1-50 parts of ethylene glycol,

[0010] 1-2 parts of solid paraffin,

[0011] 0.5-2 parts of rare earth samarium compound.

[0012] The M is one or more of Ni, Co, Al, Cr, Au, and Mg, and 0.3≤x≤0.6.

[0013] Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also enhance ionic conductivity and charge-discharge cycle performance.

[0014] Furthermore, the rare earth samarium compound is one of samarium oxide, samarium carbonate and samarium nitrate. The addition of rare earth elements can effectively increase the charge and discharge capacity of the positive electrode material and improve the electrochemical performance of the material.

[0015] A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps:

[0016] (1) weighing a lithium source, a manganese source, and a compound of M according to a molecular formula of xLi2MnO3·(1-x)LiMO2 in a stoichiometric manner, mixing them, adding ethylene glycol, and then stirring and wet grinding them to mix them uniformly to form a mixed material;

[0017] (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material;

[0018] (3) sintering, crushing and sieving the initial raw materials to form a mixed powder;

[0019] (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture;

[0020] (5) The target mixture is loaded into a graphite mold, and then placed in a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product.

[0021] Furthermore, the sintering temperature in step (3) is 500-700° C., and the sintering time is 0.5-2 h.

[0022] Furthermore, the average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g.

[0023] Furthermore, in step (5), a pressure of 20 to 100 MPa is applied to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the holding time is 1 to 5 min.

[0024] The beneficial effects of the present invention are:

[0025] The lithium-rich manganese-based composite lithium battery positive electrode material provided by the present invention has the advantages of high specific capacity (up to about 300 mAh / g), first cycle voltage up to about 4.7V, stable high-temperature cycle performance, etc. The addition of rare earth elements in the present application can effectively improve the charge and discharge capacity of the positive electrode material and improve the electrochemical properties of the material. At the same time, nano-diamondene improves the mechanical, thermal and electrical properties of the polymer material, and can also improve the ionic conductivity and charge and discharge cycle performance. The present application has a simple process, low equipment strength requirements, and a short production cycle, is suitable for industrial production requirements, and has great economic value and practical value. DETAILED DESCRIPTION

[0026] Figure 1 This is an XRD diagram of Example 1 of a lithium-rich manganese-based composite lithium battery positive electrode material of the present invention;

[0027] Figure 2 This is a SEM image of Example 1 of a lithium-rich manganese-based composite lithium battery positive electrode material of the present invention;

[0028] Figure 3 This is a cycle characteristic curve of Example 1 of a lithium-rich manganese-based composite lithium battery positive electrode material of the present invention. DETAILED DESCRIPTION

[0030] The following specifically illustrates the implementation mode of the present invention in conjunction with examples. These examples are provided only for the purpose of illustration and are not to be construed as limitations of the present invention. They are only for reference and illustration purposes and do not constitute limitations on the scope of patent protection of the present invention, because many changes can be made to the present invention without departing from the spirit and scope of the present invention.

[0031] Example 1

[0032] This embodiment provides a lithium-rich manganese-based composite lithium battery positive electrode material, including the following raw materials: 50 parts of a lithium-rich manganese positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2,

[0033] Nanodiamondene 5 parts,

[0034] 7 parts of silicon dioxide,

[0035] 3 parts of iron oxide,

[0036] 25 parts of ethylene glycol,

[0037] 1 part solid paraffin,

[0038] 0.5 parts of rare earth samarium compound.

[0039] The M is Ni, 0.3≤x≤0.6.

[0040] Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also enhance ionic conductivity and charge-discharge cycle performance.

[0041] In this embodiment, the rare earth samarium compound is samarium oxide. The addition of rare earth elements can effectively increase the charge and discharge capacity of the positive electrode material and improve the electrochemical performance of the material.

[0042] A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps:

[0043] (1) According to the composition of the molecular formula xLi2MnO3·(1-x)LiMO2, a lithium source, a manganese source, and a compound of M (nickel oxide) are weighed in stoichiometric amounts, mixed, ethylene glycol is added, and then stirred and wet-milled to mix them uniformly to form a mixed material;

[0044] (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material;

[0045] (3) sintering, crushing and sieving the initial raw materials to form a mixed powder;

[0046] (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture;

[0047] (5) The target mixture is loaded into a graphite mold, and then placed in a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product.

[0048] In this embodiment, the sintering temperature in step (3) is 500-700° C., and the sintering time is 0.5-2 h.

[0049] In this embodiment, the average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g.

[0050] In this embodiment, in step (5), a pressure of 20 to 100 MPa is applied to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the holding time is 1 to 5 min.

[0051] Example 2

[0052] This embodiment provides a lithium-rich manganese-based composite lithium battery positive electrode material, including the following raw materials: 50 parts of a lithium-rich manganese positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2,

[0053] Nanodiamondene 5 parts,

[0054] 7 parts of silicon dioxide,

[0055] 3 parts of iron oxide,

[0056] 25 parts of ethylene glycol,

[0057] 1 part solid paraffin,

[0058] 0.5 parts of rare earth samarium compound.

[0059] The M is Co, 0.3≤x≤0.6.

[0060] Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also enhance ionic conductivity and charge-discharge cycle performance.

[0061] In this embodiment, the rare earth samarium compound is samarium oxide. The addition of rare earth elements can effectively increase the charge and discharge capacity of the positive electrode material and improve the electrochemical performance of the material.

[0062] A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps:

[0063] (1) According to the composition of the molecular formula xLi2MnO3·(1-x)LiMO2, a lithium source, a manganese source, and a compound of M (CoCO3) are weighed in stoichiometric amounts, mixed, ethylene glycol is added, and then stirred and wet-milled to mix them uniformly to form a mixed material;

[0064] (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material;

[0065] (3) sintering, crushing and sieving the initial raw materials to form a mixed powder;

[0066] (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture;

[0067] (5) The target mixture is loaded into a graphite mold, and then placed in a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product.

[0068] In this embodiment, the sintering temperature in step (3) is 500-700° C., and the sintering time is 0.5-2 h.

[0069] In this embodiment, the average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g.

[0070] In this embodiment, in step (5), a pressure of 20 to 100 MPa is applied to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the holding time is 1 to 5 min.

[0071] Example 3

[0072] This embodiment provides a lithium-rich manganese-based composite lithium battery positive electrode material, including the following raw materials: 50 parts of a lithium-rich manganese positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2,

[0073] Nanodiamondene 5 parts,

[0074] 7 parts of silicon dioxide,

[0075] 3 parts of iron oxide,

[0076] 25 parts of ethylene glycol,

[0077] 1 part solid paraffin,

[0078] 0.5 parts of rare earth samarium compound.

[0079] The M is Cr, 0.3≤x≤0.6.

[0080] Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also enhance ionic conductivity and charge-discharge cycle performance.

[0081] In this embodiment, the rare earth samarium compound is samarium oxide. The addition of rare earth elements can effectively increase the charge and discharge capacity of the positive electrode material and improve the electrochemical performance of the material.

[0082] A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps:

[0083] (1) According to the composition of the molecular formula xLi2MnO3·(1-x)LiMO2, a lithium source, a manganese source, and a compound of M (CrO3) are weighed in stoichiometric amounts, mixed, ethylene glycol is added, and then stirred and wet-milled to mix them uniformly to form a mixed material;

[0084] (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material;

[0085] (3) sintering, crushing and sieving the initial raw materials to form a mixed powder;

[0086] (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture;

[0087] (5) The target mixture is loaded into a graphite mold, and then placed in a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product.

[0088] In this embodiment, the sintering temperature in step (3) is 500-700° C., and the sintering time is 0.5-2 h.

[0089] In this embodiment, the average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g.

[0090] In this embodiment, in step (5), a pressure of 20 to 100 MPa is applied to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the holding time is 1 to 5 min.

[0091] Example 4

[0092] This embodiment provides a lithium-rich manganese-based composite lithium battery positive electrode material, including the following raw materials: 50 parts of a lithium-rich manganese positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2,

[0093] Nanodiamondene 5 parts,

[0094] 7 parts of silicon dioxide,

[0095] 3 parts of iron oxide,

[0096] 25 parts of ethylene glycol,

[0097] 1 part solid paraffin,

[0098] 0.5 parts of rare earth samarium compound.

[0099] The M is Au, 0.3≤x≤0.6.

[0100] Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also enhance ionic conductivity and charge-discharge cycle performance.

[0101] In this embodiment, the rare earth samarium compound is samarium oxide. The addition of rare earth elements can effectively increase the charge and discharge capacity of the positive electrode material and improve the electrochemical performance of the material.

[0102] A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps:

[0103] (1) According to the composition of the molecular formula xLi2MnO3·(1-x)LiMO2, a lithium source, a manganese source, and a compound of M (Au2O3) are weighed in stoichiometric amounts, mixed, ethylene glycol is added, and then stirred and wet-milled to mix them uniformly to form a mixed material;

[0104] (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material;

[0105] (3) sintering, crushing and sieving the initial raw materials to form a mixed powder;

[0106] (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture;

[0107] (5) The target mixture is loaded into a graphite mold, and then placed in a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product.

[0108] In this embodiment, the sintering temperature in step (3) is 500-700° C., and the sintering time is 0.5-2 h.

[0109] In this embodiment, the average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g.

[0110] In this embodiment, in step (5), a pressure of 20 to 100 MPa is applied to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the holding time is 1 to 5 min.

[0111] Example 5

[0112] This embodiment provides a lithium-rich manganese-based composite lithium battery positive electrode material, including the following raw materials: 50 parts of a lithium-rich manganese positive electrode substrate with a molecular formula of xLi2MnO3·(1-x)LiMO2,

[0113] Nanodiamondene 5 parts,

[0114] 7 parts of silicon dioxide,

[0115] 3 parts of iron oxide,

[0116] 25 parts of ethylene glycol,

[0117] 1 part solid paraffin,

[0118] 0.5 parts of rare earth samarium compound.

[0119] The M is Mg, 0.3≤x≤0.6.

[0120] Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also enhance ionic conductivity and charge-discharge cycle performance.

[0121] In this embodiment, the rare earth samarium compound is samarium oxide. The addition of rare earth elements can effectively increase the charge and discharge capacity of the positive electrode material and improve the electrochemical performance of the material.

[0122] A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps:

[0123] (1) According to the composition of the molecular formula xLi2MnO3·(1-x)LiMO2, a lithium source, a manganese source, and a compound of M (MgCO3) are weighed in stoichiometric amounts, mixed, ethylene glycol is added, and then stirred and wet-milled to mix them uniformly to form a mixed material;

[0124] (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material;

[0125] (3) sintering, crushing and sieving the initial raw materials to form a mixed powder;

[0126] (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture;

[0127] (5) The target mixture is loaded into a graphite mold, and then placed in a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product.

[0128] In this embodiment, the sintering temperature in step (3) is 500-700° C., and the sintering time is 0.5-2 h.

[0129] In this embodiment, the average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g.

[0130] In this embodiment, in step (5), a pressure of 20 to 100 MPa is applied to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the holding time is 1 to 5 min.

[0131] Performance Test:

[0132] The test results of Examples 1 to 5 are shown in the following table:

[0133] Example Discharge specific capacity (mAh / g) <![CDATA[Tap density (g / cm 3 )]]> Example 1 300.1 1.21 Example 2 284.1 1.17 Example 3 286.7 1.08 Example 4 275.6 1.02 Example 5 279.8 1.13

[0134] The discharge specific capacity was measured at 2.0-4.7V and 0.1C rate.

[0135] XRD, SEM and cycle performance tests were performed on Example 1. It was found that the main phase was lithium-rich manganese, and the crystallinity was high, the grains were relatively uniform, and the cycle performance was relatively stable. The results are as follows Figure 1-3 As shown, after comparison, it is found that Example 1 is the best example of the present application, showing excellent physical and chemical properties.

[0136] The lithium-rich manganese-based composite lithium battery positive electrode material provided by the present invention has the characteristics of high liquid absorption rate, good thermal shrinkage rate, excellent electrical conductivity and charge-discharge cycle performance. Nanodiamondene improves the mechanical, thermal and electrical properties of polymer materials, and can also improve the liquid absorption rate and thermal shrinkage rate of the diaphragm, and improve the ionic conductivity and charge-discharge cycle performance of the diaphragm. At the same time, the production process is simple, low in cost, high in quality, and has great economic and practical value.

[0137] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A lithium-rich manganese-based composite lithium battery positive electrode material, characterized in that: The raw materials include the following components: 5-100 parts of lithium-rich manganese positive electrode substrate with molecular formula xLi2MnO3·(1-x)LiMO2, Nanodiamondene 1-10 parts, 1-15 parts of silicon dioxide, 2-5 parts of iron oxide, 1-50 parts of ethylene glycol, 1-2 parts of solid paraffin, 0.5-2 parts of rare earth samarium compound, The M is one or more of Ni, Co, Al, Cr, Au, and Mg, 0.3≤x≤0.6, The rare earth samarium compound is one of samarium oxide, samarium carbonate and samarium nitrate. A method for preparing a lithium-rich manganese-based composite lithium battery positive electrode material comprises the following steps: (1) weighing a lithium source, a manganese source, and a compound of M according to a molecular formula of xLi2MnO3·(1-x)LiMO2 in a stoichiometric manner, mixing them, adding ethylene glycol, and then stirring and wet grinding them to mix them uniformly to form a mixed material; (2) adding silicon dioxide, iron oxide, solid paraffin, and rare earth samarium compound to the mixed material, adding ethylene glycol again for secondary stirring, and grinding to form an initial raw material; (3) sintering, crushing and sieving the initial raw materials to form a mixed powder; (4) mixing and stirring the mixed powder and nanodiamondene, and adding stearamide dispersant and ethanol solvent for wet grinding to form a target mixture; (5) loading the target mixture into a graphite mold, and then placing it into a spark plasma sintering furnace for low-temperature rapid sintering, crushing, and screening to obtain a target product. The sintering temperature in step (3) is 500-700°C, and the sintering time is 0.5-2h. The average particle size distribution D50 of the target product in step (5) is 1 to 10 μm; the tap density is 1 to 1.8 g / cm 3 ; Specific surface area is 8.2~12.5m 2 / g, Step (5) applies a pressure of 20 to 100 MPa to the target mixture for the entire sintering process; the vacuum degree is 10-1 to 10-3 Pa; the sintering temperature is 800 to 900°C, the heating rate is 50 to 300°C / min, and the insulation time is 1 to 5 min.

Citation Information

Patent Citations

  • Lithium and manganese-rich cathode material of lithium ion battery and preparation method of cathode material

    CN104241634A

  • Manganese-based composite positive electrode material for lithium ion battery, and preparation method thereof

    CN108448075A

  • Lithium-rich manganese-based / graphene composite cathode material, preparation method thereof and application thereof

    CN110165181A

Cited By

  • A method for preparing a lithium-rich manganese-based positive electrode material by using ultrafast joule heat shock

    CN122627484A